Boundary Between Bacterial Mesophilism and Thermophilism - Bausum, Howard T. (1965)
Bausum, Howard T. (Fort Detrick, Frederick, Md.), and Thomas S. Matney. Boundary between bacterial mesophilism and thermophilism. J. Bacteriol. 90:50–53. 1965.—The temperature boundary between bacterial mesophilism and thermophilism has been identified as 44 to 52 C. Facultative thermophiles growing in the mesophilic range require a brief period of adaptation at intermediate temperatures before gaining the capacity to initiate growth at thermophilic temperatures. Obligate mesophiles cannot grow in the thermophilic temperature range, but obligate thermophiles may show limited growth at temperatures as low as 41 C.